齿轮啮合过程中接触应力的精确分析 - 杨凡; 孙首群; 于建华; 满微微 (Jixie chuandong)
The influence factors of contact stress in meshing process are researched. Two-dimensional （2D） and three-dimensional （3D） finite element model are established and the variety of contact stress is achieved respectively. The difference between the calculation results of 2D and 3D FEM are compared,the more reasonable and exact contact stress distributions on gear tooth are obtained. The numerical results indicate that the contact stress distributions are not uniform along the tooth width direction.